(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2022)
The present paper gives the comparative study of change in relativistic frequency of Hawking radiation due to XRBs and AGN categories of black holes and concludes that the relativistic change in frequency of Hawking radiation due to XRBs is greater than to that of AGN category of spinning black holes.